Dichroic mirror pulses for optimized higher-order atomic Bragg diffraction - D. Pfeiffer; M. Dietrich; P. Schach; G. Birkl; E. Giese (Physical Review Research)
Increasing the sensitivity of light-pulse atom interferometers progressively relies on large-momentum transfer techniques. Precise control of such methods is imperative to exploit the full capabilities of these quantum sensors. One key element is the mitigation of deleterious effects such as parasitic paths deteriorating the interferometric signal. In this Letter, we present the experimental realization of dichroic mirror pulses for atom interferometry, its scalability to higher-order Bragg diffraction, and its robustness against initial momentum spread. Our approach selectively reflects resonant atom paths into the detected interferometer output, ensuring that these contribute to the signal with intent. Simultaneously, parasitic paths are efficiently transmitted by the mirror and not directed to the relevant interferometer outputs. This method effectively isolates the desired interferometric signal from noise induced by unwanted paths. It can be readily applied to existing setups capable of higher-order Bragg diffraction.